Challenges and Solutions for Islamic Education Lecturers in Learning in the Digital Era - Slamet Riyadi; Ditha Alvira; Herman Taufik; Muchlis Muchlis; Muhammad Faizul Husnayain (EDUJAVARE: International Journal of Educational Research, 2026)
In today's digital era, students have extensive access to various learning resources via the internet, so the role of educators is no longer the sole source of knowledge, but rather as facilitators, guides, and directors in the learning process. This study aims to analyze the challenges and solutions faced by Islamic Religious Education (PAI) lecturers in learning in the digital era. The development of information technology has changed the learning paradigm, requiring lecturers to adapt to the use of technology without neglecting Islamic values. This study used a descriptive qualitative approach with PAI lecturers selected through purposive sampling. Data collection techniques were conducted through in-depth interviews, observation, and documentation. Data analysis used an interactive model that included data reduction, data presentation, and conclusion drawing, as well as data validity testing through triangulation and member checking. The results showed that the main challenges faced by PAI lecturers include limited digital competency, changes in student characteristics that tend to prefer interactive learning, and the challenge of maintaining values and ethics amidst the flow of digital information. Possible solutions include improving digital competency through training, implementing innovative learning models such as blended learning and flipped classrooms, and utilizing creative and contextual digital media. Furthermore, institutional support in providing infrastructure and supporting policies is also an important factor in successful learning.